The Dark Side of the Moon: Rivalry and Riots for Shelter and OccupationBetween the Greek and Jewish Populations in Multi-ethnic Nineteenth-century Odessa - Sifneos, Evridiki (The Historical Review/La Revue Historique, 2007)
This article aims to shed light on the competition between Greeks and Jews in the multi-ethnic context of Odessa, suggesting that rivalry was "the dark side of the moon", while the other side was characterised by conviviality, basically through assimilation and upper-class solidarity.